The impact of Brexit on the commodity futures volatility in the United Kingdom - Hong, Suwen (2018)
There are limited studies on commodity futures markets volatility regarding Brexit so this dissertation aims to analyze the commodity futures markets volatility before and after Brexit in the UK. Besides, this dissertation adds to the limited studies on Brexit, other than stock and foreign exchange markets. London Metal Exchange and Intercontinental Exchange are used to analyze in three sub-sectors, which are base metals (aluminum, copper, zinc, nickel, lead and tin), energy (Brent crude, gasoil and natural gas) and softs (coffee, sugar, cotton, cocoa and orange juice). BEKK Multivariate GARCH is employed to obtain hedge ratios, then the hedge ratios are applied into hedged equation. Next, values from the hedged equation are computed into variance and standard deviation to measure the volatility. Findings show that copper, gasoil and cotton are the most volatile commodity, whereas nickel, Brent crude and sugar are the least volatile commodity within the three sub-sectors respectively. However, gasoil has the highest volatility change and nickel has the lowest volatility change among all the commodities after Brexit. Besides, the energy sector is the most volatile market and the base metals sector is the least volatile market in the event of Brexit. OLS is used to reaffirm the findings using BEKK Multivariate GARCH and the findings hold.